English Live Caption in a Javanese Shadow Puppet Theatre: Systemic Functional Linguistics for Appraising the Beauty of Sagopi - Dyah Ayu Nila Khrisna; Djatmika Djatmika (Langkawi: Journal of The Association for Arabic and English, 2022)
In the field of simultaneous translation, live captioning has not been sufficiently touched by research. There have been shifts in translating characterization due to this being done in real-time and on the spot. It is critical that target readers or viewers get the same impression of a character's personality as portrayed in the original work. Consequently, translations of literary plays must be thoroughly checked for fidelity. The objective of the study is to undertake an in-depth analysis of the live captioning provided in "The Life Struggle of Sagopi" puppet theater. It compares the character portrayal of the protagonist, Sagopi, in the original play and the translation. Employing a content analysis technique, all of the utterances describing Sagopi's beauty were collected. As a method for analyzing the data, the theory of Appraisal was utilized. When the described Appraisal elements are identical to those in the original, the characterization would be considered equivalent. The analysis reveals that the live captions do not fully represent the portrayal of Sagopi. While the description of Sagopi's beauty in the shadow puppet performance is detailed, the English live caption does not reflect this. In the target language, deletions and shifts of appraisals indicate the changes. The lack of culturally relevant terminologies and the time lag between the puppeteer's oral utterances and the translator's typing speed during live captioning are the main causes of the problem. Furthermore, live captioning is time and space-constrained. Almost always, it is a condensed version of the oral source text. This demonstrates how difficult it is to achieve the same level of appraisal as the original. This is not to suggest that viewers have no right to a high-quality translation. Despite its shortcomings, the written text in the form of a live caption is regarded as the finest way for foreigners to enjoy a puppet show.